Gender Based Differences in Epidemiologic and Clinical Profile of Adult Vitiligo - Anaba, Ehiaghe L (Journal of Diseases, 2019)
Vitiligo, an asymptomatic de-pigmenting skin disease occurs in both males and females. It is not readily known if differences in clinical and socio-demographic features exist between male and female vitiligo patients. To document gender based differences in socio-demographic (age at onset, area of onset, family history of vitiligo) and clinical characteristics (type of vitiligo, severity of disease, activity of lesions, area affected) of adult Nigerian vitiligo patients. This was a retrospective cross-sectional study of 76 adult vitiligo patients who attended the Dermatology Outpatient Clinic of the University College Hospital, Ibadan from January 2005 to December 2009. A questionnaire designed for the study was used to document the relevant information. Data was analyzed using SPSS version 16. Prevalence of vitiligo was 4.5%, 44 males (57.9%) and 32 females (42.1%) were seen. Mean age at onset was 34.6 ±17.1 years with a range of 1-78 years. The face and scalp were the commonest areas of vitiligo occurrence in both genders. There were differences in clinical characteristics however, they were not statistically significant. Significate difference was found in level of education, self-medication and duration of disease. There are some differences in clinical profile between male and female adult vitiligo patients.